MNEs and the Sustainable Development Goals: what do first steps reveal? - Rob van Tulder; Jan Anton van Zanten (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
The Sustainable Development Goals (SDGs) provide a coherent framework for the implementation of business models that aim at the needs of society. Corporate support for the SDGs is positive, but also relatively reactive. Policies are proposed to help companies embrace SDGs aimed at "doing good," instead of "avoiding harm."
Keywords: 330